The Legal Framework for Investment in Telecommunications Services - Jasim, Rusul Jafar; Hussein, Akram Mohammed (Journal of Ecohumanism, 2024)
Through reviewing the investment topics related to communications, we found the extent of technical, economic and organizational expansion witnessed by the communications sector. Perhaps one of the most important reasons for this expansion is the multiplicity and diversity of investment activities available to communications companies, as the communications sector has become a direct center for attracting capital owners to invest their money in one of the investment projects related to communications. Accordingly, this research will address the definition of the legal framework for investment in communications services, specifically investment in the field of mobile phone services and marketing communications services.